The Management Of Training On Industrial Internship ( A Site Study At State-Owned Vocational High School 1 Jogonalan) - Hardewi, Is (2012)
The purpose of this research in general is to know the characteristics of the management system of training on industrial internship at state owned Vocational High School 1 Jogonalan. Sub-objectives of the study include, (1) to describe the characteristics of the students in program of training on industrial internship at state owned Vocational High School 1 Jogonalan, (2) to describe the characteristics of the trainer in the implementation of Training on Industrial Internship at State-owned Vocational High School 1 Jogonalan. This study was conducted by with qualitative research. It produces descriptive data in the form of words written and spoken of the people and behaviors that can be observed. The research sources or informants applied in the research are students at second levael from accounting, administration and marketting program as a subject of the program, trainer as a supervisor at industry, the principal as the decision maker of the program. The result of the research showed that VHS Jogonalan 1 students were ready to participate in the training on industrial internship. There were supported by their knowledge, basic skills and ability, and mentality. Collaboration with industries and institution patnership with state owned VHS Jogonalan 1 was very good. It is proved by Means of Understanding letters (MoU) that have been authorized by school and industries or institution partnership. The students' activities in industry accomplished properly as they were sustained by their ability and competences. It can be perceived by the numbers of students contributed in program of internship at industry . The trainer also performed the activities well, particularly in conducting the students during practice in industry. The trainer continuously provided guidance to the students before accomplishing assignments and verified the result.The ultimate assesment embraces discipline, willingness and motivation of work, the quality of work, initiative and creativity in their work, as well as attitudes and behaviors. In the final accomplishment, most students were very satisfactory in contributing the program. As it is very beneficial in selecting future career. Trainer and industry were also satisfied with the students' contribution.